Anais Do Congresso Brasileiro De Automática 2020 2020
DOI: 10.48011/asba.v2i1.1557
|View full text |Cite
|
Sign up to set email alerts
|

Robust state derivative feedback LMI-based designs for discretized systems.

Abstract: This work addresses novel Linear Matrix Inequality (LMI)-based conditions for thedesign of discrete-time state derivative feedback controllers. The main contribution of this work consists of an augmented discretized model formulated in terms of the state derivative, such that uncertain sampling periods and parametric uncertainties in polytopic form can be propagated from the original continuous-time state space representation. The resulting discrete-time model is composed of homogeneous polynomial matrices wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…and (44) can be rewritten as (34) with polynomial homogeneous matrices given by (36), which implies that discretized model (12) (37). As aforementioned, the computation of the exact values for the residuals is a hard task.…”
Section: X(kt) − φ(T)f(𝛼 1 )mentioning
confidence: 99%
See 2 more Smart Citations
“…and (44) can be rewritten as (34) with polynomial homogeneous matrices given by (36), which implies that discretized model (12) (37). As aforementioned, the computation of the exact values for the residuals is a hard task.…”
Section: X(kt) − φ(T)f(𝛼 1 )mentioning
confidence: 99%
“…Taking into account Lemma 3, the parameter-dependent matrices Ξ(𝛼) in (31) can also be recast in terms of homogeneous polynomial matrices Ξ [g] (𝛼). For the matrices Ξ[g] (𝛼) and Ξ[g] (𝛼), a detailed formulation is given in Leandro et al [37], where the later can be found by replacing T(𝛼 2 ) with T(𝛼 2 ). As a consequence, the homogeneous polynomial matrix Ξ[g] (𝛼) is then presented here for clarity…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
See 1 more Smart Citation